Efeitos locais e sistêmicos da terapia de fotobiomodulação sobre o desempenho muscular e recuperação pós exercício - Machado, Caroline Monteiro (2019)
INTRODUCTION: Recent studies with photobiomodulation therapy (TFBM) have showing positive results in delaying skeletal muscle fatigue and improving the status of biochemical markers related to skeletal muscle recovery when these therapies were applied before exercise. Some manufacturers have suggesting that TFBM has systemic effects, however, to the best of our knowledge it still was not tested whether TFBM exerts any systemic effects on human skeletal muscle performance. OBJECTIVE: To verify the local and systemic effects of TFBM on skeletal muscle performance and post-exercise recovery when applied before an exercise protocol in healthy male subjects. METHODS: It was carried out a randomized, triple-blinded, placebo-controlled trial, with voluntary participation of thirty healthy subjects. These volunteers were randomly distributed in 3 experimental groups (Placebo-Control Group, Systemic Group and Local Group) who received TFBM in 6 sites of the quadriceps muscle in both legs. Parameters related to volunteers’ exercise performance (peak torque during maximum voluntary contraction – MVC), late muscle pain through visual analogue scale (VAS) and muscle damage through creatine kinase (CK) activity were analyzed. Analysis were performed before (baseline), and at 1 minute, 1, 24, 48, 72 hours after the end of eccentric exercise protocol for fatigue induction. RESULTS: TFBM irradiation at exercised leg (local group) was able to significantly improve exercise performance of volunteers (p<0.05), to prevent the increase in CK activity (p<0.05), prevent the increase blood lactate (p<0.05) and decrease in pain (p<0.05) compared to both placebo-control and systemic groups. The outcomes observed for irradiation on systemic group were similar to observed in placebo-control group both in MVC, CK activity, Lactate e VAS (p>0.05). CONCLUSION: Our outcomes demonstrate one more time that local irradiation of TFBM is able to enhance exercise performance and to decrease muscle damage. There were not observed any positive outcomes irradiating the non-exercised leg (systemic group), which demonstrates how important is to irradiate locally the muscles involved in the exercise activity in order to achieve ergogenic effects through TFBM.